Correlation of alvarado scoring system with C - Reactive protein and leukocytes in the diagnosis of acute appendicitis - Burak Hasgul; Serhat Karaman; Murat Ayan; Nilay Sefa Ucar (Medicine Science, 2019)
In this study, we aimed to investigate the correlation of Alvarado scoring with C-reactive protein and leukocytes and the reliability of Alvarado scoring, and to guide clinicians for patient management. This study was planned as a prospective study. Data of the patients who presented to the emergency department with abdominal pain and diagnosed with acute appendicitis, and the control group were examined by the researchers. After a detailed physical examination, patients Alvarado scoring parameters and laboratory outcomes were recorded. Pathologic outcomes of the patients who were considered to have acute appendicitis and operated were studied. A different pathology other than appendicitis was found in 13 (15.1%) of 86 patients who were considered to have acute appendicitis and operated (negative appendectomy). According to the pathologic outcomes of the patient group, the most common cause of acute appendicitis was found to be fecalloids by 84.9%. Whereas simple appendicitis was observed in 85% of the patients, perforation was found in 8.2%. The most common finding of physical examination was right iliac fossa (95.8%), while the most common symptom was nausea / vomiting (67.1%) the in the cases of acute appendicitis. Among the Alvarado scoring parameters, fever was the least common symptom by 12.4%. In our study, we found a significant correlation between Alvarado scoring and leukocytes both in patients and control groups. Whereas there was no correlation between Alvarado scoring and C-reactive protein in the patient group, there was a correlation between these two parameters in the control group. There was a weak negative correlation between Alvarado scoring and acute appendicitis. Although Alvarado scoring has been reported to be a guiding scoring system in management of patients considered to have acute appendicitis, in our study this scoring was found to be statistically insignificant. Alvarado scoring alone is not sufficient in establishing a diagnosis, and the diagnosis should be supported by laboratory tests or imaging methods. [Med-Science 2019; 8(1.000): 132-7]